Corporate effective tax rates for R&D The case of expenditure-based R&D tax incentives - González Cabral, Ana Cinta (OECD Publishing, 2021)
R&D tax incentives have become a widely used policy tool to promote business R&D. How do they shape firms' incentives to invest in R&D? This paper contributes a methodology to construct forward-looking effective tax rates for an R&D investment that reflect the value of expenditure-based R&D tax incentives. The new OECD estimates cover 48 countries and consider the case of large profitable firms, accounting for the bulk of R&D in most economies. The results provide new insights into the generosity of R&D tax incentives from the perspective of firms that decide on whether or where to invest in R&D (extensive margin) and the level (intensive margin) of R&D investment. The generosity of the favourable tax treatment of R&D is shown to vary at the intensive and extensive margins, highlighting differences in countries' strategies to support R&D through the tax system
Keywords: Finance and Investment; Taxation; Science and Technology